Estimation and prediction of pollutant concentrations involved in nitrogen oxides cycles a doubly stochastic model - Kazimierczyk, Piotr; Szabłowski, Paweł J.; Twardowska, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to present a new type of model that forecasts the instantaneous concentrations of several species involved in the NOx cycle in the lower atmosphere, by treating the trajectories of pollutants' particles as trajectories of stochastic processes, and which takes all the advantages of filtering theory.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka